The Ability to Meet the Elderly’s Basic Needs for Healthy Ageing in Low- and Middle-Income Countries - Putri, Amelia Anggarawati; Lestari, Chairunnisa Niken (KnE Life Sciences, 2018)
by 2050, 80% of the elderly worldwide will be living in low- and middle-income countries. Demographic shift is challenging low- and middle-income countries to ensure their social and health systems are ready for the elderly. This paper aims to identify what basic needs have to be fulfilled for the elderly to experience healthy ageing especially in low- and middle-income countries. The method used for this study was a literature review of official reports and statistics, and scientific journals. The first basic need is financial security. In countries where pension systems are weak, the elderly live in extended households sharing the budget with their children. The second need is for personal security and safety. Issues such as injuries, crime, and disasters become prominent. The third need is for mental health. The number of people with dementia in low- and middle-income countries is predicted to be four times higher than in high-income countries by 2050. The fourth need is for accessible health care. The biggest challenge for low- and middle-income countries is the ability for the elderly to afford health care. The last need is self-actualization. These needs have not yet been met and still challenge low- and middle-income countries even though they are essential for healthy ageing and elderly welfare.